2022
DOI: 10.1021/acs.jmedchem.1c02221
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design for Nitroreductase (NTR)-Responsive Proteolysis Targeting Chimeras (PROTACs) Selectively Targeting Tumor Tissues

Abstract: The catalytic properties of proteolysis targeting chimeras (PROTACs) may lead to uncontrolled off-tissue target degradation that causes potential toxicity, limiting their clinical applications. The precise control of this technology in a tissue-selective manner can minimize the potential toxicity. Hypoxia is a hallmark of most solid tumors, accompanied by elevated levels of nitroreductase (NTR). Based on this character, we presented a type of NTR-responsive PROTACs to selectively degrade proteins of interest (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 43 publications
(63 reference statements)
0
44
0
Order By: Relevance
“…34). 274 Unlike Zhang's group, the control group they used was (1-methyl-2-nitro-1 H -imidazol-5-yl)methyl and was linked to the E3 ligase ligand VHL. They also found that the degrader 214 can rapidly release the active PROTAC 215 under hypoxia conditions and the activated PROTAC 215 can efficiently induce the degradation of EGFR protein.…”
Section: Design Of Conditionally Controlled Protacsmentioning
confidence: 99%
“…34). 274 Unlike Zhang's group, the control group they used was (1-methyl-2-nitro-1 H -imidazol-5-yl)methyl and was linked to the E3 ligase ligand VHL. They also found that the degrader 214 can rapidly release the active PROTAC 215 under hypoxia conditions and the activated PROTAC 215 can efficiently induce the degradation of EGFR protein.…”
Section: Design Of Conditionally Controlled Protacsmentioning
confidence: 99%
“…A similar hypoxia-activated prodrug strategy was also investigated by Zhu et al in a very recent work. 121 In this case, the authors incorporated a (1-methyl-2-nitro-1 H -imidazol-5-yl)methyl group on the hydroxyl of VHL ligand. Starting from the EGFR-directed PROTAC 40 , they synthesized the PROTAC prodrug 41 ( Figure 15 ), which as a result was unable to degrade EGFR under normoxic conditions.…”
Section: Combining Protac and Drug Conjugate Modalitiesmentioning
confidence: 99%
“…A similar hypoxia-activated prodrug strategy was also investigated by Zhu et al in a very recent work . In this case, the authors incorporated a (1-methyl-2-nitro-1 H -imidazol-5-yl)­methyl group on the hydroxyl of VHL ligand.…”
Section: Combining Protac and Drug Conjugate Modalitiesmentioning
confidence: 99%
“…The inherent microenvironment provides the potential to endogenously release active drugs. 26 Research in this field for PROTAC release is still in the early stages. Recently, hypoxia-activated PROTACs have been reported.…”
mentioning
confidence: 99%
“…Recently, hypoxia-activated PROTACs have been reported. 27 Herein, considering the ROS differences between cancerous and normal cells, ROS responsive Pre-PROTACs were designed. We envisioned that these ROS-activated Pre-PROTACs would efficiently degrade the target proteins in cancer cells and have little effect on normal cells due to the elevated ROS levels in cancer cells.…”
mentioning
confidence: 99%